Геоелектричні аномалії та алмазоносність Українського щита - Кулік, С.М.; Бурахович, Т.К. (Видавничий дім "Академперіодика" НАН України, 2007)
The anomalies of high electrical conductivity in the Earth's crust and the upper mantle of the Ukrainian shield are spatially correlated with the existence of diamonds. It is possible that the Kirovograd, Priazovian, Volynian, Chernivtsi-Korosten anomalies are indicators of the areas perspective as for the presence of diamonds.